Fluence distribution of terrestrial gamma ray flashes observed by the Fermi Gamma‐ray Burst Monitor. Issue 10 (3rd October 2013) - Tierney, D.; Briggs, M. S.; Fitzpatrick, G.; Chaplin, V. L.; Foley, S.; McBreen, S.; Connaughton, V.; Xiong, S.; Byrne, D.; Carr, M.; Bhat, P. N.; Fishman, G. J.; et al.
<x xml:space="preserve">Abstract</x> [1] The observed γray fluence distribution of terrestrial gamma ray flashes (TGFs) detected by the Fermi Gamma‐ray Burst Monitor (GBM) is altered by instrumental effects. We perform corrections for dead time, pulse pileup, and detection efficiency in a model‐independent manner. A sample of 106 GBM TGFs is selected to include both TGFs that triggered GBM and weaker TGFs found using an off‐line search. Detector dead time and pulse pileup lower the observed fluence of each TGF and the detection efficiency causes weaker TGFs to have a lower probability of detection than brighter TGFs. Monte Carlo simulations are performed in each case to correct for these effects. The corrected fluence distribution is well fit with a power law of index α=−2.20±0.13. This is consistent with previous estimates using other techniques. Neither a high‐fluence cutoff nor a low‐fluence limit is found. The fluence distribution is also expressed in units of TGF h−1 km−2 versus photons cm−2 per TGF.